3D FTO Inverse Opals@Hematite@TiO2 hierarchically structured Photoanode for Photoelectrochemical Water Splitting. (29th September 2017) - Chai, Xiaobo; Zhang, Haifeng; Cheng, Chuanwei
Abstract: In this work, we report the fabrication of a novel 3D F:SnO2 (FTO) inverse opals@Hematite@TiO2 hierarchical photoanode for photoelectrochemical (PEC) water spliting. In this architecture design, the 3D FTO inverse opals supporting hematite nanorods not only provide large surface area and voids space, but also offer direct and fast electron transport pathways. Moreover, the TiO2 overlayer on hematite nanorods can further improve charge transfer and separation efficiency. As a result, the FTO inverse opals@Hematite@TiO2 hierarchically structured electrode exhibits a dramatically improved PEC performance with photocurrent densities of 1.3 mA cm −2 at 1.23 V versus reversible hydrogen electrode of 2.0 mA cm −2 at 1.6 V under a simulated 1 sun illumination (100 mW cm −2 ).